Dataset: Cold storage extends mango postharvest life by modulating abscisic acid levels and sugar composition - Alamar, M. Carmen; O'Brien, Ciara; Falagán, Natalia; Kourmpetli, Sofia; Terry, Leon A. (Cranfield University, 2026)
Mango is traditionally classified as a climacteric fruit, in which ethylene and abscisic acid (ABA) play central roles in ripening. Mango fruit is cultivated only in tropical and some subtropical regions, therefore, to meet global demand, cold storage is widely used during transport, followed by a ripening period. This study evaluated the effects of simulated commercial transit cold storage (9 °C, > 85% relative humidity [RH]) used during the sea freight supply chain from the Southern hemisphere to the UK, by comparing the two main mango fruit cultivars (‘Keitt’ and ‘Kent’) imported into the UK market. Fruit were ripened with and without prior cold storage (control) and the synthesis and catabolism of key ripening regulators (ABA and its metabolites) as well as associated changes in quality attributes (internal colour, firmness, individual sugar content) were investigated. Cold storage delayed firmness loss, extending the postharvest life from 10 to 12 days to 29 days. ABA accumulated throughout ripening in control fruit but was depleted in cold-stored fruit for both cultivars, indicating its central role in mango ripening; cold storage fundamentally altered ABA dynamics by suppressing accumulation and modifying spatial distribution and conjugation patterns in a cultivar and pulp dependent manner. Additionally, sugar metabolism was altered, likely affecting taste, and meaning that, in cold-stored fruit, sugar content no longer correlated with total soluble solids (TSS). These findings highlight ABA as a potential target for postharvest management and underscore the need for integrated quality indices beyond TSS to improve fruit evaluation and reduce losses in global supply chains.
Keywords: plant growth regulators; sugars; total soluble solids; firmness; Magnifera indica; colour; gene expression